Suppressor mutations in Rpf2-Rrs1 or Rpl5 bypass the Cgr1 function for pre-ribosomal 5S RNP-rotation - Thoms, Matthias; Mitterer, Valentin; Hurt, Ed (Nature Communications, 2018)
During biogenesis of the eukaryotic 60S ribosome, a large rotational movement of the 5S RNP is required to achieve its mature position. By analyzing extragenic suppressors of crg1—a key factor required for rotation—the authors provide mechanistic insight into a key step of ribosome biogenesis.